Molecular characterization of wild tomato mosaic virus and chilli veinal mottle virus mix‐infecting chilli pepper in China. Issue 2 (20th December 2022) - Hu, Yongliang; Chen, Yuqin; Su, Xiaoxia; Huang, Jiawei; Yin, Hongxing; Zhang, Jie; Zhang, Zhongkai; Ding, Yong; Zheng, Kuanyu
Abstract: The present study described molecular characterization of two potyviruses: wild tomato mosaic virus Dehong isolate (WTMV‐Dh) and chilli veinal mottle virus Dehong isolate (ChiVMV‐Dh) mix‐infection chilli pepper and assessed their mix‐infection on chilli pepper. Transcriptome next‐generation sequencing technology (NGS) and RT‐PCR were used to obtain the complete genome sequences of the abovementioned two viruses. The results showed that the complete sequence of WTMV‐Dh is 9675 nucleotides (nt) in length and encodes a complete polyprotein of 3075 amino acids (aa). The WTMV‐Dh polyprotein shares 76.1%–82.6% nt and 85.3%–89.5% aa identities with three previously reported WTMV isolates. The complete sequence of ChiVMV‐Dh is 9736 nt in length and encodes a complete polyprotein with 3, 089 aa. ChiVMV‐Dh polyprotein shares 80.8%–92.2% nt and 85.3%–95.6% aa identities with previously reported ChiVMV isolates. Following phylogenetic analysis based on the polyprotein sequences of potyviruses revealed that WTMV‐Dh clustered with the Vietnam strain WTMV‐Laichau, while ChiVMV‐Dh clustered with several ChiVMV Sichuan isolates. The mix‐inoculation experiment showed that the mix‐infection of these two viruses has more severe symptoms than single‐infection.